PENGEMBANGAN E-LKPD BERBASIS KEARIFAN LOKAL MENGGUNAKAN PLATFORM WIZER.ME UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS IV MI NURUL ISLAMIYAH MLIDEG KABUPATEN BOJONEGORO - Alviati, Umu; Amreta, Midya Yuli; Rofi'ah, Firda Zakiyatur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to describe the development process of local wisdombased E-LKPD using the wizer.me platform, determine the development results, and assess the effectiveness of E-LKPD in improving the learning motivation of grade IV students at MI Nurul Islamiyah Mlideg. The problems identified include low student learning motivation in IPAS learning, lack of understanding of moral values, unfamiliarity with Bojonegoro local traditions, and limited attractive and interactive teaching materials. This research uses the 4D development model consisting of Define, Design, Development, and Disseminate stages. Data collection techniques include observation, interviews, questionnaires, and tests with qualitative and quantitative data analysis. The results show that the E-LKPD development process was designed attractively with ice breaking videos, learning material videos, an various types of questions using easily understood language. Expert validation results show instrument expert 78% (feasible), material expert 80% (feasible), language expert part I 84% (very feasible), language expert part II 88% (very feasible), student responses 96% (very feasible), and N-Gain test 0.5 (moderate). The overall average of 84% indicates that local wisdom-based E-LKPD using the wizer.me platform is very feasible and practical for use in learning, especially in building civilized society material.